(3f)+2=11

Simple and best practice solution for (3f)+2=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3f)+2=11 equation:


Simplifying
(3f) + 2 = 11

Reorder the terms:
2 + (3f) = 11

Solving
2 + (3f) = 11

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + (3f) = 11 + -2

Combine like terms: 2 + -2 = 0
0 + (3f) = 11 + -2
(3f) = 11 + -2

Combine like terms: 11 + -2 = 9
(3f) = 9

Divide each side by '3'.
f = 3

Simplifying
f = 3

See similar equations:

| -8st+5t+2u-1=8t+9u-9 | | 170=45t | | 10b-9-3b=2 | | 170-t=45 | | 45=170t | | 4x-6-5x-5=x-4 | | 100=x^2+10x+25 | | (9x+59)+(6x-6)+(3x+8)+(12x+29)=360 | | /8+/50+2/2= | | 162=-8x+10 | | -7(p+1)+3=-18-5p | | -4u+4u-9= | | 28x-7=26 | | -6x^2+54x-48=0 | | 8+x=x-1 | | -3u-8u= | | t-81+50=-7 | | 3(3x-6)+4(-5x-1)=-8 | | 13+x=47 | | 4x-6-5x+5=x-4 | | -10n+12=-6n-16 | | -4(2x+3)=-8x-12 | | 8u^2+10u^2= | | 8(3x-6)+4(-5x-1)=-8- | | 36a^4+108a^3+77a-12a-9= | | 2x+8-20=-3x-(-18) | | x+(x+1)+(x+2)+(x+3)=26 | | (4x+8)+(9x-43)+(8x+9)+(5x+48)=360 | | -19+11x=9+10x | | x+6-2x=15 | | (5a)-1+a=11 | | 2(2x-10)=4(x-10) |

Equations solver categories